THE EFFECT OF VOCABULARY TOWARDS WRITING SKILL WITH READING SKILL AS MODERATING EFFECT - Paskalina Widiastuti Ratnaningsih; Catharina Clara (Universitas Bengkulu, 2021)
Vocabulary is one of the English components that need to be mastered for acquiring writing and reading. Writing needs various vocabularies to build different sentences. Reading needs understanding of different meaning of vocabularies based on the context in the sentence. Hence, vocabulary is important in English language learning to support writing and reading. Regarding the importance of vocabulary, writing, and reading, the aim of this research is to test the effect of vocabulary mastery towards writing ability in English. It is also to test moderating effect of reading ability in strengthening or weakening the relation. This study used moderated regression analysis (MRA). Then, this research used the test as research instrument. The instruments had been valid and also reliable. Classical assumption tests were used before the research analysis. The samples were Management students of semester four and six. Descriptive analysis towards each variable is used to know students’ ability in English. To analyze the effect of independent variables towards dependent variable, it used linear regression analysis. To analyze moderating effect, it used moderating regression analysis. From this research result, it was proved that vocabulary had positive significant effect towards writing skill. Reading skill moderated the relation of vocabulary towards writing skill. Further research can focus on experimental research of vocabulary, writing, and reading.